Glucose-responsive peptide coacervates with high encapsulation efficiency for controlled release of insulin - Lim, Zhi Wei (2020)
A new glucose-responsive insulin delivery system is fabricated using biomimetic peptide coacervates derived from the Humboldt squid (Dosidicus Gigas) beak. Both insulin and glucose oxidase are coencapsulated within coacervate microdroplets. The glucose oxidase quickly responds to increasing glucose levels to generate a local acidic environment, thereby rapidly triggering the dissociation of pH-sensitive coacervates to release the insulin cargo. The rate of insulin release is dependent on the glucose level, increases under hyperglycemic conditions, and decreases under normoglycemic conditions. This glucose responsiveness mimics pancreatic β-cell function by releasing insulin according to glucose levels.